The effects of Electronic Word Of Mouth (EWOM) and Brand-Awareness to govern the advancement of Brand Attitude towards the Brand Repurchase Intention: A case of Mobile brands in Pakistan - Dr. Moeed Ahmad Sandhu; Ayesha Saleem; Asad Ali (iRASD Journal of Management)
This research explored effects of Electronic word-of-mouth and brand-awareness as a moderator to regulate the advancement of brand attitude towards the brand repurchase intention. EWOM communication has been an exciting explorationin the area of branding and there is an emerging attention on the effectiveness of EWOM communication. This research used a quantitative approach and the data was collected through questionnaire. Model and hypothesis were drawn by the researcher to comprehend the attitude towards the brand repurchase intention. Regression analysis technique was used to identify the cause and effect relationshipamongstconstructs and to determine significance in the results. The study was conducted on 300 consumer respondents and research results were analysed by using SPSS and PLS. It was found that positive EWOM with moderating effect of  brand awareness strongly influences development of positive brand attitude and consequently cause repurchase intention towards that brand. Several theoretical contributions and practical implication are also discussed. Interestingly,it was found that the effect of EWOM will become stronger when individuals are aware that others will evaluate their behaviour due to social conformity.